Adaptation of Ushafa clay, Abuja, as a suitable replacement for bentonite in the foundry industry (2008)
This work investigated the possible use of Ushafa clay in Abuja, Nigeria as a suitable replacement for bentonite clay in foundry use. Moulding sand mixes with compositions of 8,10 and 13%. Ushafa clay, silica sand and 5,7,8,9,10 and 11% coal dust additives were mulled. From each mix, cylindrical specimens were prepared and subjected to permeability, shatter index, compression and shear strength tests . The results from the Ushafa mix were compared with results from bentonite mixes. The results showed that moulding sand compositions having 13%. Ushafa clay, and coal dust additions of 8% produced specimens with good permeability, dry strength, green strength and collapsibility for foundry use. This work has confirmed the possible use of Ushafa clay as suitable replacement for bentonite binder in foundry